PELATIHAN PERHITUNGAN BREAK EVEN POINT BAGI USAHA TANAMAN HIDROPONIK - Br. Ginting, Suriani; Pandia, Sonya Enda Natasha S.; Wailan’An, Evi Juita (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Hydroponics is soilless plant cultivation which develops plants by providing the nutrients needed by the plants given in the water supply. The purpose of this Break Even Point Calculation (BEP) training is to help Berdikari Farm to conduct financial analysis in determining sales units to achieve BEP. (break even point). This training will also be useful in planning to determine profit. The stages of implementing Community Service activities are carried out with the stages of conducting training through the stages of identifying needs, presenting material, discussing and asking questions. . The results of the achievement of the community service program that has been implemented is that this training activity as a whole received a very good response from Berdikari Farm, especially in terms of carrying out a break-even analysis so that through this activity Berdikari Farm can plan a minimum amount of sales so as not to experience a loss.